1986
DOI: 10.1002/jso.2930330414
|View full text |Cite
|
Sign up to set email alerts
|

Villous tumors of the duodenum and ampulla of vater

Abstract: Polypoid epithelial tumors of the duodenum and ampulla of Vater are rarely diagnosed preoperatively without wide application of fiberoptic endoscopy. The symptoms are nonspecific. Only a high index of suspicion will lead to early diagnosis. Life-threatening complications and increased incidence of malignant transformations are associated with delayed diagnosis. This paper reviews 11 patients (nine previously unreported) with villous tumor of the ampulla of Vater and two with this neoplasm in the duodenum. It a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…Für die Tumordiagnostik ist der Grad der Zelldifferenzierung von Bedeutung. Celik et al (11) kamen in der Auswertung ihres Materials auf 17% leichte, 33% mäßige und 50% schwere Zellatypien in den villösen Adenomen. Kniemeier et al (15) fanden leichte Zellanomalien bei 50% der Adenome und nur bei 12% schwere Zellatypien.…”
Section: Patienten Und Methodikunclassified
“…Für die Tumordiagnostik ist der Grad der Zelldifferenzierung von Bedeutung. Celik et al (11) kamen in der Auswertung ihres Materials auf 17% leichte, 33% mäßige und 50% schwere Zellatypien in den villösen Adenomen. Kniemeier et al (15) fanden leichte Zellanomalien bei 50% der Adenome und nur bei 12% schwere Zellatypien.…”
Section: Patienten Und Methodikunclassified
“…The cytologic features of benign, malignant, and other lesions, e.g., villous adenoma, however, has not been well described. 6 -' 5 To the best of our knowledge only one other case of villous adenoma diagnosed by brush cytology has been previously reported. The case reported by Howell et al (their case #3) was initially reported as benign but had many of the features that we have described in our four patients.…”
Section: Normal Adenomatous Malignantmentioning
confidence: 99%
“…The use of cytologic examination of biliary tract brush specimens obtained at the time of endoscopy as an adjunct to surgical biopsies to increase the diagnostic yield is a challenge for cytologists since the cytologic features of benign lesions, such as adenoma, have not been well described. 6 -' 5 We studied seven brush cytology specimens from four patients with villous adenomas of the ampullary region in all of whom surgical pathology and clinical follow-up was obtained.…”
mentioning
confidence: 99%
“…Great care is necessary in diagno sis, because adenomas or villous tumors have been re ported to be closely associated with carcinoma of Vater's ampulla [1][2][3]. This carcinoma has a better resectability and a more favorable postoperative outcome than other periampullary carcinomas [4], Ampullary carcinoma has a high potential of multidi rectional spread, and its prognosis is strongly related to nodal involvement and pancreatic invasion [5,6].…”
Section: Introductionmentioning
confidence: 99%